The Column Generation Technique for Public Transport Line Planning by IP-Solver - Janacek, Jaroslav; Sirc, Jan (Communications - Scientific letters of the University of Zilina, 2010)
The paper deals with an application of the column generation method to the public transport line planning making use of a common optimization environment. The authors focus on the opportunities offered by the optimization software for the column optimization and for manmachine approach to the process of line planning. The paper resumes the former approach to the transport line planning based on line selection from a large set of all sensible lines and, on the contrary to the former approach, introduces the column generation method for a new route design. A case study from practice is used to compare both approaches and to point out their advantages and disadvantages.